Terrified Girls and Furious Boys: Does the Discourse around face and eyes in British Children's Fiction Reinforce Gender Stereotypes? - Elizabeth Poynter (Universitas Sanata Dharma, 2025)
Language in context frequently reflects conscious or unconscious gender stereotypes. With children's literature, this may contribute to the development of a stereotypical gender identity. This study examines the linguistic context of two body parts, face and eyes, in two corpora of British children's fiction: adventure books aimed at 'boys and girls', and school and family stories aimed at girls only. Both corpora comprise texts from the mid-twentieth century, which is regarded as a period of strong gender polarisation, and specifically popular rather than prizewinning texts. Analysis employed LancsBox 6.0 corpus software. Faces and eyes may both be used to express emotion, and particular emotions have been associated with traditional binary gender stereotypes. It was hypothesised that these corpora would demonstrate such binary stereotyping. The study found considerable overlap between the two genres, but some distinctions suggesting that the literature for girls was somewhat less stereotyped than that aimed at a mixed readership. The expression of some emotions, such as fear and anger, tended to suggest stereotypical linking of these emotions with a particular gender, although less strongly than has been found in some other studies. It is hoped that these findings will contribute to our understanding of how a child's developing gender identity may be influenced.